Study on Method for Relative Fidelity Preservation of Seismic Data (Relative Fidelity Processing of Seismic Data, 2017)
On seismic profile, the display reliability of seismic response on lithology reservoirs is subject to the fidelity of seismic processing. Relative fidelity preservation processing of seismic data should pay attention to the following items: Protection of effective frequency band. The widening of effective band should rely on SNR of seismic data. In order to widen the low S/N seismic data to high frequency band, it is necessary to control the bandwidth and dominant frequency of the deconvolution operator. Based on the seismic pilot survey line, this chapter analyzes and discusses the effects of seismic acquisition source and observation means on the data processed by high resolution and high SNR or by relative fidelity in terms of profile reflection features and spectrum features. Compared with the profile processed by high resolution and high SNR, the profile processed by relative fidelity preservation could reflect the seismic effect on subsurface sand reservoirs quite genuinely.